Influence of term gestational age on weight: cohort study - Michelin, Nathallia Serodio [UNESP] (2021)
Objective: Identify the effect of term gestational age on birth weight and its evolution in the first year of the child's life. Method: Single cohort, concurrent, with prospective follow-up of one year, performed in Botucatu/SP. Data were collected at three moments in the child's first year of life. To analyze the weight at birth, at six and at twelve months, in function of the gestational age, including potential confounding variables, regression models with normal response were adjusted after identifying bivariate associations with p<0.20. The analyses were developed using SPSS V22. Results: Independently, early-term children were, on average, 161 g lighter at birth (beta=-161.6; 95% CI=-236.1--87.2; p<0.001), 350 g heavier at six months (beta=0.35; 95% CI=0.16-0.53; p<0.001) and 290 g heavier at twelve months (beta=0.29; 95% CI=0.04-0.50; p=0.019) than full-term children. Secondary findings: mothers of older age and who attended a larger number of antenatal consultations had heavier babies at birth; longer children at birth were heavier at six and twelve months and infants breastfed longer were lighter at twelve months. Conclusion: Full-term gestational age was associated with birth weight, at six and twelve months. Early-term children independently showed a lower birth weight and higher weight than full-term infants at six and twelve months of age.